Transition From Military Prehospital Medicine to Civilian EMS. Issue 9 (4th June 2020) - Westcott, Sally; Walrath, Benjamin; Miller, Jeremy; Trumbull, Melissa; Manifold, Craig
Abstract: Introduction: Currently, there is a disconnection between veteran military medics and the civilian Emergency Medical Services (EMS) workforce. This project aimed to characterize the rate of civilian certification among military medics, both active duty and retired, and identify perceived barriers to continuing a career in EMS after military separation. Materials and Methods: The National Association of Emergency Medical Technicians (EMTs) administered a 21-question online survey to participants. Individuals were recruited through the National Association of EMTs membership communications, Military Relations Committee members, and social media. All responses were anonymous and no identifiable information was collected. Survey questions were compiled and reported as a percentage of respondents. Free-text responses were categorized based on broad themes identified by the authors and are reported as a percentage of respondents. Results: Results included 456 veteran and active duty respondents, of whom 304 (70.7%) had prehospital experience while in the military and 250 (58.1%) had emergency department experience. Over 60% of respondents participated in combat-related duty with 37% having at least 18 months of overseas deployment. Civilian EMT certification was held by 164 (36.7%) survey participants and 170 held paramedic certification (38.1%), while 65 (14.6%) held no EMS certification. There were 119 (28.1%) respondents who stated that they did not plan to work in civilian EMS. Top selected reasons for not pursuing civilian EMS careers included: pursuing a medical career that was not prehospital (28.5%), pay disparity (18.1%), and no interest in civilian prehospital medicine (16.4%). Write in responses indicated general frustration with maintaining certification and a desire for advanced certification (AEMT, paramedic) to be supplied by the military prior to transitioning to a civilian workforce as many respondents felt their military-endowed skills and experiences were better aligned with these advanced EMS licenses. Conclusion: The majority of survey respondents held an EMS certification of some kind and suggests that recent efforts to supply military medics with civilian certifications have been largely successful. However, there is still a large portion that remains noncertified or expresses disinterest with entering the civilian workforce. Generally, many of those certified feel their military scope of practice exceeded civilian EMT certification and requested AEMT or paramedic licensure opportunities while still active duty military.